High-Performance Inverted Structure Broadband Photodetector Based on ZnO Nanorods/PCDTBT:PCBM:PbS QDs - Upadhyay, D.C.; Upadhyay, R.K.; Singh, A.P.; Jit, S. (Institute of Electrical and Electronics Engineers Inc., 2020)
This article reports the performance improvement of a broadband photodetector using penetrating ZnO nanorods arrays (NRAs)-based electron transport layer (ETL) into a nanocomposite active layer of poly-[ {N}-9'' -heptadecanyl-2.7-carbazole-alt-5.5-(4',7'-di-2-thienyl-2',1',3 -benzothiadiazole)] (PCDTBT), [6, 6]-phenyl C61 butyric acid methyl ester (PCBM), and PbS quantum dots (QDs) grown on an fluorine-doped tin oxide (FTO)-coated glass substrate. A thin layer of MoOx on the active layer was used as the hole transport layer (HTL) of the proposed photodetector. The device showed a high responsivity of 213.77, 28.57, and 7.22 A/W at three selected wavelengths in ultraviolet (380 nm), visible (550 nm), and near-infrared (860 nm) regions, respectively. High external quantum efficiency (EQE) of more than 1000% was measured for each selected wavelength at low -1.5 V external bias. The superior EQE in the proposed device was attributed to both the surface trap-induced carrier injection into the ZnO NRA and ultrafast exciton dissociation existing in the PCDTBT:PCBM system. © 1963-2012 IEEE.
Keywords: External quantum efficiency (EQE); PbS quantum dots (QDs); poly-[N-9-heptadecanyl-2.7- carbazole-alt-5.5-(4 ,7 -di-2-thienyl-2 ,1 ,3 -benzothiadia zole)] (PCDTBT):[6,6]-phenyl C61 butyric acid methyl ester (PCBM) composite; responsivity; ZnO nanorods cathode buffer layer